2022
DOI: 10.1186/s13102-022-00468-4
|View full text |Cite
|
Sign up to set email alerts
|

Injuries in alpine summer sports - types, frequency and prevention: a systematic review

Abstract: Introduction Summer alpine sports, including mountain biking, hiking and airborne pursuits, have experienced a recent surge in popularity. Accordingly, trauma associated with these activities has increased. There is a scarcity of literature exploring clinical aspects surrounding injuries. Specifically, no single article provides a general overview, as individual studies tend to focus on one particular sport. In the present study, we performed a systematic literature review to summarize existing… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 76 publications
0
7
0
Order By: Relevance
“…However, the number of fatal hiking accidents in the Austrian Alps has remained relatively stable (<10%) over the investigated time period and compared to data from scientific literature [5] , [7] . A similar trend has been shown for fatal accident outcomes in other mountain sports such as mountain climbing [14] ; concerning mountain biking, the results from literature seem to be inconsistent [15] , [16] . In the present study, men suffered from multiple types of injuries and cardiovascular events more frequently, whereas women were more likely to sustain fractures mostly involving the lower body (e.g., the ankle or foot).…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…However, the number of fatal hiking accidents in the Austrian Alps has remained relatively stable (<10%) over the investigated time period and compared to data from scientific literature [5] , [7] . A similar trend has been shown for fatal accident outcomes in other mountain sports such as mountain climbing [14] ; concerning mountain biking, the results from literature seem to be inconsistent [15] , [16] . In the present study, men suffered from multiple types of injuries and cardiovascular events more frequently, whereas women were more likely to sustain fractures mostly involving the lower body (e.g., the ankle or foot).…”
Section: Discussionsupporting
confidence: 74%
“…Furthermore, we can confirm the analysis of the previous 9-year period with the finding that men were more likely to have hiking accidents in pathless terrains, which has been previously shown to be fatal often [7] . This might be related to a possible enhanced risk-taking behavior in men, especially in male summer alpinists [16] , [21] . However, this has mostly been investigated in mountain sports other than hiking (i.e., mountain running or climbing) [22] .…”
Section: Discussionmentioning
confidence: 99%
“…[5] Studies have shown that cyclists are not immune to injury or illness. [2,[17][18][19][20][21] The range of injuries and illnesses that do occur is vast, however, the reporting of injuries varies signi cantly with a signi cant lack of homogeneity between studies and disciplines. [2,4] Injury and Illness surveillance studies in other sports are far more advanced and have seen the development of speci c warm-up routines to reduce injury risk such as FIFA 11 [22]in soccer, and Gaelic Athletic Association (GAA) 15 [23] in Gaelic games.…”
Section: Search Strategymentioning
confidence: 99%
“…[5] Studies have shown that cyclists are not immune to injury or illness. [2,[17][18][19][20][21] The range of injuries and illnesses that do occur is vast, however, the reporting of injuries varies signi cantly with a signi cant lack of homogeneity between studies and disciplines. [2,4] Injury and Illness surveillance studies in other sports are far more advanced and have seen the development of speci c warm-up routines to reduce injury risk such as FIFA 11 [22]in soccer, and Gaelic Athletic Association (GAA) 15 [23] in Gaelic games.…”
Section: Comparator (C)-not Applicablementioning
confidence: 99%